Excess weight, abdominal obesity and short stature in economically active adults from Mérida, México (Research, Society and Development, 2023)
Introduction: Overweight and obesity represent a multifactorial public health problem related to a high risk of chronic-degenerative diseases; short stature has also been associated with increased risk of obesity and metabolic diseases. Objective: to determine the relationship between excess weight, abdominal obesity and short stature in economically active adults in the city of Mérida. Methodology: Cross-sectional study carried out with a convenience sample of 1424 workers (18 to 65 years old) from companies in Mérida, Mexico. The information obtained was age, sex, weight, height, body mass index and waist circumference, which was analyzed with descriptive statistics and chi-square. Results: The sample consisted of 829 women and 595 men. Low stature was found in 26.9% (n=223) of the women and 16.7% (n=99) of the men. Most of the sample was overweight, distributed as 31.5% and 51.1% overweight and obese, respectively. Conclusions: Mérida workers have a high prevalence of overweight, obesity and abdominal obesity, conditions present in a greater proportion in those with short stature, mainly in women.